The cotton stainer's gut microbiota suppresses infection of a cotransmitted trypanosomatid parasite. Issue 16 (27th July 2018) - Onchuru, Thomas O.; Martinez, Adam J.; Kaltenpoth, Martin
Abstract: The evolutionary and ecological success of many insects is attributed to mutualistic partnerships with bacteria that confer hosts with novel traits including food digestion, nutrient supplementation, detoxification of harmful compounds and defence against natural enemies. Dysdercus fasciatus firebugs (Hemiptera: Pyrrhocoridae), commonly known as cotton stainers, possess a simple but distinctive gut bacterial community including B vitamin‐supplementing Coriobacteriaceae symbionts. In addition, their guts are often infested with the intestinal trypanosomatid parasite Leptomonas pyrrhocoris (Kinetoplastida: Trypanosomatidae). In this study, using experimental bioassays and fluorescence in situ hybridization (FISH), we report on the protective role of the D. fasciatus gut bacteria against L. pyrrhocoris . We artificially infected 2nd instars of dysbiotic and symbiotic insects with a parasite culture and measured parasite titres, developmental time and survival rates. Our results show that L. pyrrhocoris infection increases developmental time and slightly modifies the quantitative composition of the gut microbiota. More importantly, we found significantly higher parasite titres and a tendency towards lower survival rates in parasite‐infected dysbiotic insects compared to symbiotic controls, indicating that the gut bacteria successfully interfere with the establishment or proliferation of L. pyrrhocoris . The colonization of symbiotic bacteria on the peritrophic matrix along the gut wall, as revealed by FISH, likely acts as a barrier blocking parasite attachment or entry into the hemolymph. Our findings show that in addition to being nutritionally important, D. fasciatus' gut bacteria complement the host's immune system in preventing parasite invasions and that a stable gut microbial community is integral for the host's health.